Nuclear Stress in Oral Communication among EFL Speakers: Is It Important or Not? - Moedjito, Moedjito (Universitas Hamzanwadi, 2018)
This article reports a study which investigated the importance of nuclear stress in the successful oral communication among EFL speakers in the context of global intelligibility. In addition to the main objective, the present study tried to disclose the participants’ experience in learning English and their opinion about English pronunciation as well as pronunciation teaching. In order to achieve the goals of the study, the present researcher conducted a participatory research. Two types of instrument were used to collect data: a questionnaire and an in-depth interview. Prior to the in-depth interview, the questionnaire was distributed to 63 EFL participants. The main finding discovered that the EFL participants did not share their agreement on the important role of nuclear stress when speaking English. They acknowledged that meaningful vocabulary and intelligible pronunciation influenced their understanding the message being sent by the speakers. Also, the results have revealed that although the EFL participants had different durations and occasions in learning English, their oral ability was considerably good to excellent. They could improve their oral performance, particularly pronunciation, for some other factors such as listening English music, travelling, listening to Podcasts, and others.